The Development of Immunologic Competence - Ribatti, Domenico (Springer International Publishing : Imprint: Springer, 2015)
This book traces significant aspects of the history of immunology, exploring the immune system and immunodeficiency. The author recounts human hematopoietic development, and how a distinction of the immune system into thymus-dependent and thymus-independent components has been demonstrated in different animal species, including amphibians, birds, and mammals. Other themes explored in this book include discoveries about the role of the thymus of the Bursa of Fabricius in the development of immunologic competence, and observations on the changes in the lymphoid organs after bursectomy and thymectomy in chickens. Readers will discover how the bursa provides a unique microenvironment for the proliferation and differentiation of B cells, while thymectomized and irradiated animals were deficient in lymphocytes that mediated inflammatory responses, as assessed by skin graft rejection, delayed-type hypersensitivity, and graft versus host reaction. A clear perspective for understanding several diseases and also the entire lymphoid system emerges through the experiments and extensive histopathological studies of patients with primary immunodeficiency diseases that are described in these chapters. Researchers in the life sciences, in biomedicine and the history of medicine will all find something of value in this highly engaging work. It will also appeal to those with an interest in public health and neurobiology.